PENGARUH EARNING GROWTH, DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP PRICE EARNING RATIO - Abdul Hadi; Agustina Dianova; Alfiya Nur Maulidyah (Media Mahardhika, 2023)
The study aims to provide empirical data on the impact of profit growth (EG), debt toequity ratio (DER) and net income (NPM) on profitability ratios (PER) in lodging, restaurant and travel registered business entities (IDX) in 2018. The research method uses multiple regression analysis with data collection techniques through documentation. The results of the study explain that there is an effect of the debt to equity ratio and net income on the price/earnings ratio, but the development of earnings does not affect the price/earnings ratio. The impact of this research is that investors are advised to look at several other indicators besides profit (EG), debt to equity ratio (DER) and net income (NPM) to profitability ratio (PER) in representing the price earning ratio.